“Obscure” Appendiceal Orifice Polyps Can Be Challenging to Identify by Colonoscopy - Afshin Amini; Elliot Koury; Zahra Vaezi; Amirsina Talebian; Elie Chahla (Case Reports in Gastroenterology, 2020)
The primary purpose of screening colonoscopy is the detection and subsequent removal of precancerous polyps. However, effective recognition of appendiceal lesions with a standard endoscope is often challenging and is limited to the base of the cecum and appendiceal orifice. The majority of appendiceal polyps are found incidentally following an appendectomy, though rarely they may be discovered during a colonoscopy. Despite being visualized by colonoscopy, most of these polyps are generally referred for surgical resection. The risk of developing carcinoma in patients with appendiceal polyps is likely similar to that of other colonic polyps, so it is essential for the endoscopist to examine and visualize the appendiceal orifice thoroughly. Various techniques are available to the endoscopist that can increase the accuracy of colonoscopic evaluation. These include luminal inflation and deflation, looking behind and pressing haustral folds, and repetitive passage of the scope over poorly visualized areas. To our knowledge, only 3 cases have been reported in the literature describing the discovery of obscure appendiceal polyps using colonoscopic techniques. Here we describe three cases of appendiceal orifice polyps missed on initial visualization but subsequently protruded into the cecum following prolonged examination and gentle deflation in the cecum. The endoscopist should consider the possibility of an appendiceal neoplasm, especially if other colonic polyps have been found. Endoscopists should spend adequate time examining the cecum during a screening colonoscopy to expose and thoroughly examine the appendiceal region.